PENGARUH PERILAKU TENAGA KESEHATAN TERHADAP KESIAPSIAGAAN BENCANA DI KABUPATEN NIAS UTARA TAHUN 2021 - Eko Krisman Harefa; Daniel Ginting; Mido Ester J. Sitorus; Donal Nababan (Universitas Pahlawan, 2021)
Disaster is an extreme disruption of the functioning of a society that causes widespread social, material and environmental harm and exceeds the ability of affected communities to cope by using only their own resources. Events such as earthquakes, floods, and storms only become catastrophic when they are serious or affect people's lives, livelihoods and property. A hazard event (e.g. an earthquake, flood, or hurricane) becomes catastrophic when someone is injured, loses their life and livelihood, and damages infrastructure and public property. The purpose of this study is to look at the Effect of Health Workers' Behavior on Disaster Preparedness in North Nias Regency in 2020. Types of analytical research with cross sectional design. This research was conducted at the North Nias Kanupaten Health Office. This research was conducted in August 2021 at the North Nias District Health Office. The population and samples in this study were all health workers in the Office of Health As many as 63 people and sampled. Data analysis is univariate, bivariate and multivariate analysis with Chi-Square test. The results of the chi-square statistic test analysis were obtained p value = 0,000 <0.05 meaning there is an Influence of Respoden Knowledge on Disaster Preparedness in North Nias Regency year 2021. The results of the chi-square statistic test analysis were obtained p value = 0,000 <0.05 meaning there is an effect of respoden attitude on Disaster Preparedness in North Nias Regency 2021. The results of the chi-square statistical test analysis were obtained p value = 0.001 <0.05 meaning there is an Influence of Respoden Practice on Disaster Preparedness in North Nias Regency 2021. It is recommended that health workers can improve their knowledge of disaster preparedness and be more positive to prepare themselves to be involved in dealing with disasters. North Nias Regency Health Office in the form of a final report that can be the basis in consideration of improving disaster preparedness for health workers in the Office of Health. For future researchers, it is necessary to add subvariables, such as: non-mental attitudes, in order to perfect the conclusions of this study